On spectra of a certain class of quadratic operator pencils with one-dimensional linear part - Pivovarchik, V.N. (Український математичний журнал, 2007)
We consider a class of quadratic operator pencils that occur in many problems of physics. The part of such a
pencil linear with respect to the spectral parameter describes the viscous friction in problems of small vibrations
of strings and beams. Patterns in location of eigenvalues of such pencils are established. If the viscous friction
(damping) is pointwise, then the operator in the linear part of the pencil is one-dimensional. For this case, rules
in the location of the purely imaginary eigenvalues are found. Розглянуто певний клас квадратичних операторних в'язок, що виникають у багатьох задачах фізики. Лінійна за спектральним параметром частина в'язки описує в'язке тертя в задачах про малі коливання струн та стержнів.
Встановлено закономірності в розташуванні власних значень таких в'язок. Якщо в'язке тертя зосереджене в одній точці, то оператор у лінійній за параметром частині в'язки є одновимірним. Для цього випадку знайдено порядок розташування суто уявних власних значень.